Creating a system of medical and psychological rehabilitation of extreme professions representatives (firemen-rescuers as a model) - J. Chumaeva; V. Golikovа; J. Nekhoroshkova; A. Ogulenko; L. Shafran (Kazimierz Wielki University, 2015)
Chumaeva Julia, Golikovа Vladislava, Nekhoroshkova Julia, Ogulenko Alexey, Shafran Leonid. Creating a system of medical and psychological rehabilitation of extreme professions representatives (firemen-rescuers as a model). Journal of Education, Health and Sport. 2015;5(8):197-209. ISSN 2391-8306. DOI 10.5281/zenodo.28064 http://dx.doi.org/10.5281/zenodo.28064 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A197-209 https://pbn.nauka.gov.pl/works/607738 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.06.2015. Revised 15.07.2015. Accepted: 12.08.2015.   CREATING A SYSTEM OF MEDICAL AND PSYCHOLOGICAL REHABILITATION OF EXTREME PROFESSIONS REPRESENTATIVES (FIREMEN-RESCUERS AS A MODEL)   Julia Chumaeva1, Vladislava Golikovа1,2, Julia Nekhoroshkova1, Alexey Ogulenko1, Leonid Shafran1   1Ukrainian Scientific and Research Institute of Transport Medicine, Odessa, Ukraine 2Odessa National Maritime Academy, Odessa, Ukraine   Abstract Background. Working conditions of representatives of extreme professions (firemen-rescuers are a good example), are connected with disregulations and disorders of physiologic functions, fatigue accumulation and disadaptation. The medical and psychological rehabilitation is an effective way for occupational health and reliability restoration. However, last one is characterized by an empirical approach and conducted by priority of medical component, that significantly reduces effectiveness of the undertaken measures. So, it is necessary to develop a system of combined medical and psychological rehabilitation (MPR). Materials and methods. In this progect MPR was carried out in 238 specialists of three professional groups:  firemen-rescuers (146), fire-engine drivers (44) and inspectors of fire safety (48 - control). Psychophysiological examination included the computerized program "MORTEST", variant "SPAS-14" performance, answers to the individual-typological questionnaire (ITQ) and Eysenck personal test (EPT). The levels of epinephrine (Е), norepinephrine (NЕ), dopamine (DА)  and dioxyphenylalanine (DOPA) urinal excretion, the vanillylmandelic (VMA) and homovanillic acids (HVA) levels in urine were also defined. The survey is conducted three times: at the beginning, middle and the end of a 12-day rehabilitation course. Statistical data processing  was carried out by common programs in  Microsoft Excel. Results and discussion. The studies have shown that the attributes to identify individual-typological differences are indicators of extroversion-introversion and anxiety in tests ITO and EPT. The results  were divided into three clusters: extroverts with low anxiety (52.9%); ambiverts with low (27.7%) and high anxiety (19.4%). Simultaneously it was assigned different types of SAS response in the rehabilitation process: basic or balanced, epinephrinic, norepinephrinic, and with low secretory activity. Low efficiency of rehabilitation measures occurred in 40.7 ± 5,1% of surveyed firefighters with epinephrinic response type and SAS functional exhaustion. The type of SAS response allocated 3 levels of stress in fire-rescuers: adequate to professional load, with the signs of hormonal and mediatorial dissociation, and dangerous - with the depletion of all links of SAS.      Conclusion. According to the results of the performed researches it was developed a system of MPR, which allows to conduct a differentiated remediation of firemen-rescuers in the view of occupational features, individually-typological properties of the rehabilitants' personality, the nature and degree of changes in the central nervous, autonomic and hormonal systems. The developed approaches included in the elaborated Methodical Guidelines, implemented in practice. Key words: extreme professions, firemen-rescuers, medical and psychological rehabilitation, psychophysiological assessment, psychological markers, catecholamines excretion, effective measures elaboration.